Madrasah Head's Strategy for Improving Students' al-Qur`an Reading and Writing Ability at MI As'adiyah - Muammar Tasbih; Khojir Khojir; Akhmad Muadin (Universitas Muhammadiyah Enrekang, 2023)
The aim of this research is to describe the strategies used by madrasa heads in an effort to improve students' reading and writing skills of the Al-Qur'an. The research method used was qualitative with a case study approach. Data collection techniques using observation, interviews and documentation studies. The data analysis technique after the data is collected (data collection) is the Miles, Huberman and Saldana technique, with a series of analyzes in the form of data display, condensation and conclusion. Data validation using source triangulation and technique triangulation. The results of this research indicate that the madrasa head's strategy is to improve students' reading and writing skills of the al-Qur`an at MI As'adiyah. First, integrating al-Qur'an reading lessons into the masdrasah curriculum. Second, holding extracurricular lessons to read the al-Qur`an. Third, holding extracurricular learning to write the al-Qur`an. Fourth, holding MTQ (Musabaqoh Tilawatil Qur'an) within the madrasah. Fifth, include students in external madrasah MTQ. Sixth, holding training for teachers. Seventh, Discipline teachers using a reward and punishment approach.